Kemampuan Siswa SMA dalam Pemecahan Masalah Matematika berdasarkan Kemampuan Matematis dan Gender - Rina Alfiyanti; RM. Bambang; Suhartati Suhartati (Universitas Syiah Kuala, 2023)
Problem-solving constitutes a significant objective in mathematics education. However, empirical evidence indicates that students often struggle to answer non-routine math questions. Various factors, including mathematical ability and gender, can influence students' problem-solving skills. The present study aims to investigate Year 10 students' problem-solving abilities based on mathematical ability and gender. A qualitative approach with a descriptive design was employed for this research. The participants comprised 34 Year 10 students. Data collection involved administering math problem-solving tests, mathematical ability test, and interviews. The findings revealed that female students displayed greater attention to detail when answering questions. Both male and female students with low mathematical abilities exhibited limited problem-solving skills, primarily due to difficulties comprehending the information presented in the questions and formulating and executing appropriate plans. Male and female students with moderate mathematical abilities demonstrated moderate problem-solving skills, often making calculation errors and neglecting to perform thorough evaluations. Male and female students with high mathematical abilities displayed moderate problem-solving skills, mainly due to suboptimal planning resulting from the selection of inappropriate strategies. Male and female students with high mathematical abilities showcased problem-solving abilities by effectively analyzing problem information, devising appropriate plans, and conducting thorough verifications.